If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3t-20-11=11-3t
We simplify the equation to the form, which is simple to understand
3t-20-11=11-3t
We move all terms containing t to the left and all other terms to the right.
+3t+3t=+11+20+11
We simplify left and right side of the equation.
+6t=+42
We divide both sides of the equation by 6 to get t.
t=7
| 2(m-22)+3(m-3)=37 | | 7f+9=5f-9 | | 5(4-5x)=-155 | | 3-5x=10x-6x-33 | | 7(x-3)-2x=5(x-3) | | 4x+2=3(x-3)+y | | -8g+5=-9g | | 10x-(6x-2)=14 | | 24x-8=7-(3x-15) | | 1+9n=8n+10 | | (x+4)=2b^2+9b+4 | | 15=5+10(x-3) | | 15y+17=4 | | -1+5(-6k+5)=5k-5(7k+8) | | -5(2n-3)=40 | | x+5=-3-x | | 5y-1+6y=10y+7 | | 20*log(x)=10 | | 12x+3-5x+9= | | -5+z=18 | | 30x^2+60=0 | | 25x-5=35x+1 | | 10+9j=8j-j-2 | | 9+x-4=x+2+7 | | 20-5x=25 | | 7t=xfindt | | 6-4x=12-6x | | -6(4n-5)=-90 | | P-(8p-3)=4 | | 5ab+10b= | | -26=-2(1-3v)+2(8+2v) | | -7s-9=1-5s |